Organizational and economic model of innovative project managementof industrial and domestic waste disposal (Путеводитель предпринимателя, 2020)
The features of the waste recycling industry development in Russia are considered, the organizational and economic model of innovation in industrial and domestic waste is given, and a new approach to a multifaceted evaluation of innovative projects is proposed.